2012
DOI: 10.1109/tvcg.2012.202
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection and Visualization of Qualitative Hemodynamic Characteristics in Cerebral Aneurysms

Abstract: Cerebral aneurysms are a pathological vessel dilatation that bear a high risk of rupture. For the understanding and evaluation of the risk of rupture, the analysis of hemodynamic information plays an important role. Besides quantitative hemodynamic information, also qualitative flow characteristics, e.g., the inflow jet and impingement zone are correlated with the risk of rupture. However, the assessment of these two characteristics is currently based on an interactive visual investigation of the flow field, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Most techniques decompose a blood flow field into regions of similar behavior based on integral curves [2,17,23,32]. Others employ local vectors [47] or aneurysm wall properties [14,18,30].…”
Section: Partition-based Visualization Of Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Most techniques decompose a blood flow field into regions of similar behavior based on integral curves [2,17,23,32]. Others employ local vectors [47] or aneurysm wall properties [14,18,30].…”
Section: Partition-based Visualization Of Blood Flowmentioning
confidence: 99%
“…Computational fluid dynamic (CFD) simulations of blood flow play a crucial role in understanding aneurysm rupture and evaluating its risk since they provide insights into the aneurysm hemodynamics [4,7,17]. Hemodynamic parameters are evaluated as predictors for aneurysm rupture together with geometrical descriptors, wall properties, inflammatory effects, genetic predispositions, and behavioral factors.…”
Section: Introductionmentioning
confidence: 99%
“…Streamlines at cluster boundaries are displayed as representatives. Gasteiger et al employ local streamline properties to identify and group lines that constitute the inflow jet, which is correlated with aneurysm rupture [31]. R€ ossl and Theisel discuss a spectral embedding of streamlines [11].…”
Section: Automatic Flow Partitioningmentioning
confidence: 99%
“…1,2 Computational fluid dynamics analyses by using human cerebral aneurysm models suggested that inflow jets may be related to bleb formation and aneurysmal rupture. [3][4][5] Cebral et al 3 reported that most blebs formed at sites where the inflow jet impacted the aneurysmal wall, and they qualitatively classified the inflow jets of ruptured and unruptured cerebral aneurysms into concentrated and diffuse inflow jets.…”
mentioning
confidence: 99%